Workshop Tata Cara Memperoleh Nomor IRT Bagi Usaha Kecil Di Desa Pulau Panggung - Subianto, Subianto; Syahfani, Al Mubarach Yudis; Fahrizal, Dhani; Vitriani, Tia; Putri, Engga Dwi (Universitas Dehasen Bengkulu, 2022)
National food security is very important and a concern of all stakeholders. An important stakeholder in the realization of food security is MSME players as providers of food products spread throughout Indonesia. The distribution of food products is regulated by the government by setting requirements for the fulfillment of PIRT permits. The P-IRT permit is a certification stipulated by the government through Law No. 18 of 2012 emphasized by Per-BPOM No. 10 of 2021, which regulates the safety of food products from raw materials, processing, to the final product, therefore the process of making P-IRT is considered important with a complete explanation of the procedure for making a PIRT permit has changed and the existence of the Law on Job Creation No. 11 of 2020. The phenomenon of changes in the SOP (Standard Operating Procedure) involves processes based on information technology so as to produce outcomes in the form of faster services and avoid the practice of brokering.